Generation Z Entrepreneurial Intentions in the Agricultural Sector in Batam Industrial City - Saqdiah, Fatma; Sari, Suci Evita; Wirawan, Adhitomo; Putri, Ancala Laras; Sabrina, Nova; Surmayanti, Reni (Journal of Applied Business Administration, 2025)
This study aims to analyze the factors of generation Z entrepreneurial intentions in the agricultural sector in the industrial city of Batam. The population in this study is management students from 4 universities in Batam City with a total of 200 respondents. This research is a quantitative research. The method used to analyze the data is factor analysis. In this study, there are 19 variables that can be reduced to several factors with the results of the study showing that there are 5 new factors, namely economic improvement, decision-making, interest, entrepreneurship education and entrepreneurial confidence.